Anaesthetists’ knowledge of pulse contour cardiac output monitoring in a department of anaesthesiology - Mandebvu, Takudzwa Richard (My University, 2022)
Background An acceptable understanding of cardiac output measuring devices is essential for anaesthetists in order to appreciate their limitations and to safely apply their use during patient care. The aim of this study was to describe the knowledge of PiCCO among anaesthetists’ working in the Department of Anaesthesiology at the University of the Witwatersrand. Methods A cross-sectional, contextual research design was employed in this study using a self-administered questionnaire. The study population consisted of all anaesthetists working in the department. Convenience sampling was used, and completion of the questionnaire implied consent. Adequate knowledge was determined as ≥62% using the Angoff method. Results Themean (SD)score obtained was 44.5% (17.6%), with seniors obtaining a significantly higher score than juniors (51.2% vs 39.1, p =0.0001). Of the 21 (14.0%) anaesthetists who had adequate knowledge, more seniors achieved an adequate score than juniors (76.2% vs 23.8%, p=0.0022). Sixteen registrars had adequate knowledge of which 12 (75%) had completed a cardiac rotation and 4 (25%) had not, with those having completed a cardiac rotation significantly achieving an adequate score than those that had not (p=0.0005). All anaesthetists with adequate knowledge had ICU exposure (p=0.0355). Anaesthetists scored the lowest in the performing of the transpulmonary thermodilution section with a mean (SD) score of 41.6% (21.9%). Conclusion Knowledge of the PICCO cardiac output monitoring technique was inadequate in a sample of anaesthetists in an academic anaesthesiology department. Seniority, experience in cardiac anaesthesia or ICU are factors improving knowledge adequacy.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine in Anaesthesia to the Faculty of Health Sciences,School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2021